Reflection about the Phenomenological Claim Book Review of Jose Ruiz: About the Meaning of Phenomenology - Rojas Jiménez, Alejandro (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
Commentary on the attempt to save the phenomenological claim (the meaning of phenomenology) that Jose Ruiz makes in his book, trying to distinguish noesis from noema. This comment is written from the view that the milestones of phenomenology cannot be considered regardless of their methodical aspect